Debt Recovery in Firm Liquidations: Do Liquidation Trustees Matter? - Jaka Cepec; Peter Grajzl; Katarina Zajc (Center for Economic Studies and ifo Institute (CESifo), 2016)
Insolvency systems play a crucial role in protection of creditor rights, yet micro-level empirical evidence on the functioning of insolvency regimes worldwide is sparse. We investigate whether creditors' recovery of outstanding claims, a measure of ex-post efficiency of an insolvency regime, depends on the characteristics of the trustee delegated the administration of the liquidation proceedings. To this end, we draw on a novel dataset of firm liquidations from Slovenia and exploit courts' de facto random assignment of firm liquidation cases to licensed liquidation trustees. Using a wide range of specifications and controls, we find that a subset of trustee characteristics indeed matters for debt recovery. Thus, ex-post efficiency of an insolvency regime depends not only on its formal rules and procedures, but also on who implements them in practice.
Keywords: G33; K22; P37; 330; insolvency; firm liquidations; debt recovery; liquidation trustees; Slovenia